Coordination of Polyploid Chromosome Replication with Cell Size and Growth in a Cyanobacterium - Ryudo Ohbayashi (American Society for Microbiology, 2019)
ABSTRACT Homologous chromosome number (ploidy) has diversified among bacteria, archaea, and eukaryotes over evolution. In bacteria, model organisms such as Escherichia coli possess a single chromosome encoding the entire genome during slow growth. In contrast, other bacteria, including cyanobacteria, maintain multiple copies of individual chromosomes (polyploid). Although a correlation between ploidy level and cell size has been observed in bacteria and eukaryotes, it is poorly understood how replication of multicopy chromosomes is regulated and how ploidy level is adjusted to cell size. In addition, the advantages conferred by polyploidy are largely unknown. Here we show that only one or a few multicopy chromosomes are replicated at once in the cyanobacterium Synechococcus elongatus and that this restriction depends on regulation of DnaA activity. Inhibiting the DnaA intrinsic ATPase activity in S. elongatus increased the number of replicating chromosomes and chromosome number per cell but did not affect cell growth. In contrast, when cell growth rate was increased or decreased, DnaA level, DnaA activity, and the number of replicating chromosomes also increased or decreased in parallel, resulting in nearly constant chromosome copy number per unit of cell volume at constant temperature. When chromosome copy number was increased by inhibition of DnaA ATPase activity or reduced culture temperature, cells exhibited greater resistance to UV light. Thus, it is suggested that the stepwise replication of the genome enables cyanobacteria to maintain nearly constant gene copy number per unit of cell volume and that multicopy chromosomes function as backup genetic information to compensate for genomic damage. IMPORTANCE Polyploidy has evolved many times across the kingdom of life. The relationship between cell growth and chromosome replication in bacteria has been studied extensively in monoploid model organisms such as Escherichia coli but not in polyploid organisms. Our study of the polyploid cyanobacterium Synechococcus elongatus demonstrates that replicating chromosome number is restricted and regulated by DnaA to maintain a relatively stable gene copy number/cell volume ratio during cell growth. In addition, our results suggest that polyploidy confers resistance to UV, which damages DNA. This compensatory polyploidy is likely necessitated by photosynthesis, which requires sunlight and generates damaging reactive oxygen species, and may also explain how polyploid bacteria can adapt to extreme environments with high risk of DNA damage.